(untitled) (Fiep Bulletin - online, 2014)
The purpose of the present study was to investigate the physical activity recommended by health professionals and the use of this approach as a treatment for hypertensive patients. Hypertensive patients (n=20), physical education teachers (n=10) and doctors (n=10) participated in this study. Doctors and teachers recognized the importance of physical activity in the management of hypertension, believing that regular exercises can improve the quality of life. Just 70% of the doctors indicated the exercise practice to their patients. According to hypertensive individuals, the more indicated treatments by doctors were medicines (85%) and physical activity (65%). Among the patients, 55% exercised as a hypertension treatment. Approximately 50% of active hypertensive patients reduced the anti-hypertensive medicines dosages. Although 16 hypertensive patients (80%) reported improvement in their quality of life, due to the exercise practice,in a direct question, the WQHOQOL questionnaire results did not show significant differences in the quality of life between hypertensive patients that performed or not regular exercise. Our results demonstrated that despite health professionals know the importance of physical activity practice for hypertensive patients, there is no regular indication of exercises as a hypertension treatment. It is important to emphasize that among the investigated patients, nearly half, did not practice exercise to control HAS. These results demonstrated a disclosure between health professional’s knowledge and recommendations and the patients practice of physical activity in the treatment of hypertension.